Typification and nomenclatural notes on twenty-three names of Buddleja (Schrophulariaceae) - O'leary, Nataly (Phytotaxa, 2015)
Twenty-three Buddleja names, either accepted species or recognized synonyms, are here lectotypified, or a typification remark is provided. Nomenclatural notes are also included, specifying the legitimacy of names of Buddleja.